The plasticity of cardiac sympathetic nerves and its clinical implication in cardiovascular disease - Kanazawa, Hideaki; Fukuda, Keiichi (Frontiers in Synaptic Neuroscience, 2022)
The heart is electrically and mechanically controlled by the autonomic nervous system, which consists of both the sympathetic and parasympathetic systems. It has been considered that the sympathetic and parasympathetic nerves regulate the cardiomyocytes’ performance independently; however, recent molecular biology approaches have provided a new concept to our understanding of the mechanisms controlling the diseased heart through the plasticity of the autonomic nervous system. Studies have found that cardiac sympathetic nerve fibers in hypertrophic ventricles strongly express an immature neuron marker and simultaneously cause deterioration of neuronal cellular function. This phenomenon was explained by the rejuvenation of cardiac sympathetic nerves. Moreover, heart failure and myocardial infarction have been shown to cause cholinergic trans-differentiation of cardiac sympathetic nerve fibers via gp130-signaling cytokines secreted from the failing myocardium, affecting cardiac performance and prognosis. This phenomenon is thought to be one of the adaptations that prevent the progression of heart disease. Recently, the concept of using device-based neuromodulation therapies to attenuate sympathetic activity and increase parasympathetic (vagal) activity to treat cardiovascular disease, including heart failure, was developed. Although several promising preclinical and pilot clinical studies using these strategies have been conducted, the results of clinical efficacy vary. In this review, we summarize the current literature on the plasticity of cardiac sympathetic nerves and propose potential new therapeutic targets for heart disease.